(untitled) (Naturalistic: Jurnal Kajian dan Penelitian Pendidikan dan Pembelajaran, 2025)
Technological developments are a challenge for the world of education, including in the learning process, which requires various digital platforms, such as Quizzizz. This research aims to analyze the literature regarding Quizizz as a learning media and evaluation tool at the elementary school level. This research uses a systematic literature review through five stages: determining the study topic, searching for articles, selecting the article, analyzing the literature, and drawing conclusions. In this study, we analyzed 24 articles related to the focus of the study, namely quizizz in elementary school learning. These articles are selected articles published from 2019 to 2024. The literature study results show that: 1) The Quizizz platform was developed as a learning media because it has a presentation feature consisting of various attractive displays to make the presentation media more interactive. 2) The Quizizz platform is generally used as an evaluation tool. The platform has many features for learning assessment, such as multiple choice assessments, open questions, matching questions, and categorizing questions. Furthermore, the feature includes flexible assessments with images, videos, and audio answers. 3) In general, using the Quizizz platform impacts student learning outcomes; in other words, students’ understanding increases after studying material through Quizizz. Apart from that, the use of Quizizz also has an impact on students’ learning motivation, enthusiasm, and skill development. Based on this, Quizizz is an important platform for teachers to develop innovative learning, develop various skills, and prepare students to face the challenges of the times and technological developments